2010
DOI: 10.7589/0090-3558-46.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hyaluronidase to Improve Chemical Immobilization of Free-ranging Polar Bears (Ursus maritimus)

Abstract: ABSTRACT:We assessed the efficacy and safety of hyaluronidase to improve chemical immobilization of free-ranging polar bears (Ursus maritimus) captured from helicopter by remote drug delivery along the Ontario coast line of northwestern James Bay and southern Hudson Bay during September 2005 and October 2007. We used a single blind study design in which one person prepared and loaded all darts without the shooter knowing whether hyaluronidase (150 IU per dart) or sterile water was added to the immobilizing dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…For the low dose etorphine and azaperone treatment group with 7500 IU HA the time to immobilization was lower, and range smaller than for the control doses, indicated a potential dose sparing effect, as more rapid uptake would result in a faster achievement of the required blood concentrations for immobilization. This supports the conclusion of Cattet & Obbard () who found that the addition of HA reduced the total dose of xylazine/zolazepam/tiletamine required for immobilisation of free‐ranging polar bears. However, it is also possible that the effective concentration required for the immobilization of wildebeest is probably lower than the current recommended dose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the low dose etorphine and azaperone treatment group with 7500 IU HA the time to immobilization was lower, and range smaller than for the control doses, indicated a potential dose sparing effect, as more rapid uptake would result in a faster achievement of the required blood concentrations for immobilization. This supports the conclusion of Cattet & Obbard () who found that the addition of HA reduced the total dose of xylazine/zolazepam/tiletamine required for immobilisation of free‐ranging polar bears. However, it is also possible that the effective concentration required for the immobilization of wildebeest is probably lower than the current recommended dose.…”
Section: Discussionsupporting
confidence: 89%
“…). In addition to speeding up immobilisation times, studies in polar bears have also suggested that the addition of HA to combinations reduces the amount of immobilizing agents required (Cattet & Obbard ). Unfortunately none of these studies were designed in a sufficiently robust manner to conclusively prove the benefit of presence of the HA in the dart mixture as they relied on the use of parallel study designs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, all double-dart injections hit the target below the control darts. Shooting drugs from a distance greater than 20 m protects the shooter from huge and dangerous animals such as elephants, bears, and rhinoceros while maintaining an acceptable 32-cm gap between two darts [5,8].…”
Section: Resultsmentioning
confidence: 99%
“…It has been applied to use with an auto-syrinx dart to deliver the drug to many animals with a shorter shooting range than the dart gun [4]. Dart gun injection is a widely accepted and routine procedure for administering anesthesia to various animals, including dangerous animals [5,6]. In large animals such as elephants, the dart gun injection is vital to manage the violence caused by musth elephant and wild elephant-human conflicts.…”
Section: Introductionmentioning
confidence: 99%